2015
DOI: 10.1093/migration/mnv008
|View full text |Cite
|
Sign up to set email alerts
|

The winner takes it all: Internal migration, education and wages in Ethiopia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…These data are nationally representative, but only capture migration across zonal borders, not movement within zones and woredas, thus underestimating the extent of internal migration and missing important processes of small‐scale urbanization happening within traditionally rural, agrarian areas . Nevertheless, these data provide an initial sketch of internal mobility patterns over the last two decades, to complement a small but growing literature on internal migration in Ethiopia (see Blunch and Laderchi ).…”
Section: The Ethiopian Contextmentioning
confidence: 86%
See 1 more Smart Citation
“…These data are nationally representative, but only capture migration across zonal borders, not movement within zones and woredas, thus underestimating the extent of internal migration and missing important processes of small‐scale urbanization happening within traditionally rural, agrarian areas . Nevertheless, these data provide an initial sketch of internal mobility patterns over the last two decades, to complement a small but growing literature on internal migration in Ethiopia (see Blunch and Laderchi ).…”
Section: The Ethiopian Contextmentioning
confidence: 86%
“…In general, those moving to or leaving urban areas tend to be more highly educated than rural‐rural migrants and non‐migrants (Table ; Figure ). Other studies in Ethiopia have found that internal migrants tend to be more highly educated than non‐migrants (Tegegne and Penker ; Bezu and Holden ), and Blunch and Laderchi () found that migrants obtain higher returns to their education than non‐migrants. These authors note that in, addition to economic opportunity, educational facilities in urban areas can be an attractive factor.…”
Section: The Ethiopian Contextmentioning
confidence: 95%
“…Increased wealth may increase unmet need or increase contraceptive use, as higher socio‐economic status is positively associated with a preference for smaller family size (Adebowale & Palamuleni, 2014). Other economic analyses of migration in Ethiopia have demonstrated that returns to education are greater for those who migrate to urban areas (Blunch & Laderchi, 2015; de Brauw, Mueller, & Woldehanna, 2018). While migration in sub‐Saharan Africa has been characterised by circulation of refugees and seasonal labour migrants throughout regions, the brain drain of more highly educated and skilled migrants from rural to urban areas or to wealthier countries within regions is also a common phenomenon (Adepoju, 2006, 2008).…”
Section: Theoretical Framework For Fertility Behaviourmentioning
confidence: 99%
“…In the case of the latter, research has shown that higher educational attainment is often accompanied by increased earning potential and more ambitious aspirations; resulting in a tendency among educated rural inhabitants to migrate to urban areas in search of new opportunities [81]. Evidence of this can be seen in a recent analysis of a nationally representative household survey in Ethiopia, which found that internal migrants had both a higher level of education and higher earning potential than their non-migrant counterparts [82]. Given that reclassification is accompanied by improvements in the standard of living, one can also imagine a situation where public health investment results in lower mortality rates, leading to further natural increase and a larger stock of future migrants.…”
Section: Examining the Dynamic Interplay-the Indirect Contributionsmentioning
confidence: 99%